Vitamin D Promotes Ferroptosis in Colorectal Cancer Stem Cells via SLC7A11 Downregulation. (16th February 2023) - Guo, Shuang; Zhao, Wei; Zhang, Weihao; Li, Shuai; Teng, Guoxin; Liu, Lan
Abstract : Colorectal cancer stem cells (CCSCs) play important roles in the prognosis, chemoresistance, and treatment failure of colorectal cancer (CRC). Ferroptosis is an effective treatment for CCSCs. Vitamin D (VD) reportedly inhibits colon cancer cell proliferation. However, information on the relationship between VD and ferroptosis in CCSCs is not well documented. In this study, we aimed to understand the effect of VD on ferroptosis in CCSCs. To this end, we treated CCSCs with different concentrations of VD and performed spheroid formation assay and transmission electron microscopy and determined cysteine (Cys), glutathione (GSH), and reactive oxygen species (ROS) levels. Furthermore, functional experiments, western blotting, and qRT-PCR were performed to explore the downstream molecular mechanisms of VD in vitro and in vivo . Results showed that VD treatment significantly inhibited the proliferation of CCSCs and reduced the number of tumour spheroids in vitro . Further evaluations showed that the VD-treated CCSCs exhibited significantly higher ROS levels and lower levels of Cys and GSH as well as thickened mitochondrial membranes. Furthermore, the mitochondria in CCSCs were narrowed and ruptured after VD treatment. These results indicated that VD treatment significantly induced ferroptosis in CCSCs. Further exploration showed that SLC7A11 overexpression significantly attenuated VD-induced ferroptosis in vitro and in vivo . Hence, we concluded that VD induces ferroptosis in CCSCs by downregulating SLC7A11 in vitro and in vivo . These results provide new evidence for the therapeutic use of VD in treating CRC and new insights into VD-induced ferroptosis in CCSCs.